Moralitas Anti-Korupsi dalam Hadis: Kajian Tematik terhadap Penyalahgunaan Kekuasaan - Nurul Fahmi Silitonga; Nurhikmah Hasibuan (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2025)
Corruption and collusion are critical issues that undermine governmental integrity and public trust. From an Islamic perspective, the Prophet Muhammad's traditions emphasize that every leader bears a trust (amanah) which must be upheld with justice, honesty, and moral integrity. This study aims to analyze anti-corruption principles in the Hadith through a qualitative library research approach and thematic (maudhu'i) analysis. Primary data were obtained from canonical Hadith collections, while secondary sources included classical commentaries and contemporary scholarly articles. The thematic analysis indicates that prohibitions against abuse of power, bribery, and collusion are explicitly reflected in the Hadith, highlighting leaders' moral accountability to both God and society. The findings demonstrate the relevance of Hadith-based ethical values in strengthening transparent, accountable, and just governance practices.